2020
DOI: 10.7759/cureus.9507
|View full text |Cite
|
Sign up to set email alerts
|

Serum Procalcitonin in Patients With Combined Lung Cancer and Idiopathic Pulmonary Fibrosis (LC-IPF)

Abstract: Background Procalcitonin (PCT) is a potential biomarker for sepsis and acts as a guide to antibiotic administration. Previous studies showed that lung cancer (LC) may increase serum PCT levels. However, no studies addressed serum PCT in patients with combined LC and idiopathic pulmonary fibrosis (IPF): LC-IPF. We aimed to evaluate the significance of serum PCT in patients with LC-IPF. Methods A total of 137 patients with IPF who had complete follow-up data were reviewed. They were categorized into two groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The discrepancy in mortality rates between our study and the TRAIGE study may have resulted from differences in the studied populations and follow-up periods. Because patients with concurrent IPF and lung cancer were reported to have higher serum PCT levels than those with IPF alone, 51 to rule out the interfering effect of lung cancer, we excluded IPF patients who had concurrent lung cancer before enrolment or developed lung cancer during the follow-up period. Our results suggest that serum PCT in IPF patients should be evaluated at a concentration above 0.05 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy in mortality rates between our study and the TRAIGE study may have resulted from differences in the studied populations and follow-up periods. Because patients with concurrent IPF and lung cancer were reported to have higher serum PCT levels than those with IPF alone, 51 to rule out the interfering effect of lung cancer, we excluded IPF patients who had concurrent lung cancer before enrolment or developed lung cancer during the follow-up period. Our results suggest that serum PCT in IPF patients should be evaluated at a concentration above 0.05 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Through the analysis of keywords, the current research hotspots in the field of respiratory diseases appear to be sepsis, pneumonia, and infections. However, according to indepth analysis of the literature, increasingly, more and more studies are examining the relationship between PCT and other diseases of the respiratory system, such as the value of PCT in the diagnosis and prognosis of lung cancer patients (10,11,(21)(22)(23)(24). Studies have shown that even if patients with lung cancer are not co-infected, the average serum PCT levels were higher than that of non-infected patients without lung cancer, and the higher the PCT levels, the worse the prognosis (10,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, severely ill patients often have lung infections and PCT is required as a reference for clinical diagnosis and disease monitoring (6)(7)(8)(9). Furthermore, some studies have shown that circulating PCT levels are related to lung tumors, chronic obstructive pulmonary diseases (COPDs), asthma, and pulmonary embolisms (10)(11)(12)(13). In 2020, PCT was widely used in coronavirus disease 2019 (COVID-19) infection management world-wide (14).…”
Section: Introductionmentioning
confidence: 99%